A Randomized Controlled Trial of Group Stepping Stones Triple P: A Mixed‐Disability Trial. Issue 3 (7th January 2013) - Roux, Gemma; Sofronoff, Kate; Sanders, Matthew
Abstract : Stepping Stones Triple P (SSTP) is a parenting program designed for families of a child with a disability. The current study involved a randomized controlled trial of Group Stepping Stones Triple P (GSSTP) for a mixed‐disability group. Participants were 52 families of children diagnosed with an Autism Spectrum Disorder, Down syndrome, Cerebral Palsy, or an intellectual disability. The results demonstrated significant improvements in parent‐reported child behavior, parenting styles, parental satisfaction, and conflict about parenting. Results among participants were similar despite children's differing impairments. The intervention effect was maintained at 6‐month follow‐up. The results indicate that GSSTP is a promising intervention for a mixed‐disability group. Limitations of the study, along with areas for future research, are also discussed.